Erlinda PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA - Erlinda Erlinda (JURNAL PENDIDIKAN ROKANIA, 2017)
This action research generally aims to improve the learning outcomes of Indonesian in the fourth grade students through the implementation of demonstration method in the first semester of SDN 003 Rambah. The data in this study were collected using tests, student observation sheets, teacher observation sheets, and field notes. The type of research is classroom action research. The research procedure consists of planning, execution, observation and reflection. The results revealed that preliminary results showed that students' absorption in the first cycle of meeting 1 was 66.6 (Less) and the first cycle of meeting 2 was 68.6 (Enough) to be the average of Cycle I (67.6) whereas cycle II the 1st meeting is 75.7 (Enough) and the second cycle of meeting 2 is81.8 (Good) so the average cycle II (86.35). For complete learning individually in cycle I (50.00%) and cycle II complete (86,35%). Based on the research, it is concluded that the demonstration method can improve the learning result of Indonesian in the fourth grade students of SD Negeri 003 Rambah.